Participatory approaches: a facilitator's guide - VSO (VSO, 2004)
This book provides a set of guidelines for people who will be involved in participatory processes and projects with specific design focus on VSO (Voluntary Services Overseas) volunteers. It looks at appropriate levels of participation; pitfalls of participatory approaches (PA); b est practice in facilitation; and tools for participation. The guide i s organised into three parts (I) Principles, (II) Methods and (III) To olkit. Part I gives a background to PA with a comparative analysis of PA in relation to top-down approaches, and within the range of PAs; lo oks at the role PA in VSO; discusses how to facilitate participatory p rocesses with multiple stakeholders; presents a framework for PA on di fferent levels of participation; and examines key facilitation skills needed to support participatory activities. Part II collates a range o f participatory methods that have been used successfully in the field by VSO volunteers. Methods are categorised according to this suitabili ty for use at different stages of a project process. Examples are also given of methods that can be used for specific purposes, such as part icipatory organisational appraisal and gender/diversity analysis. Part III gives tips on how to choose the most appropriate tool and how to organise participatory workshops and small group activities. It also s ystematically records a range of tools used by development workers all over the world with reference to what tool is appropriate in what sit uation. A profile of each tool includes guidelines on its purpose, pot ential applications and variations, as well as possible pitfalls. Illu strative case studies taken form real experiences of development worke rs in the field are also included.